An Overview of Current Research on Mesenchymal Stem Cell-Derived Extracellular Vesicles: A Bibliometric Analysis From 2009 to 2021 - Zhang, Xudong; Lu, Yimeng; Wu, Shanshan; Zhang, Siwen; Li, Shuyu; Tan, Jichun (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Mesenchymal stem cell-derived extracellular vesicles (MSC-EVs) are important mediators of intercellular communication and participate in numerous physiological and pathological processes in the body. This study aims to introduce the research status, analyze the research hotspots, and predict the development trend through bibliometric analysis of MSC-EVs. Methods: We searched all relevant literature on MSC-EVs up to 2021 in the Web of Science. R-bibliometrix, VOSviewer, and CiteSpace software were used to visualize the quantitative analysis of the published literature, including co-authorship, co-occurrence, citation, and co-citation, to provide objective presentation and predictions in the field. Results: A total of 1595 articles and reviews on MSC-EVs published between 2009 and 2021 were identified. The annual publication outputs increased at an exponential rate, reaching as high as 555 publications in 2021. China contributed the most publications (n=899, 56.36%) and had the most citations (n=24210). The United States had the strongest intensity of cooperation in this field. Shanghai Jiao Tong University had the maximum number of publications (n=79). In terms of the number of publications and co-citations, the journal of Stem cell research and therapy ranked first. Camussi G was the most productive and most cited author. The top three themes in the research area were cell biology, research experimental medicine, and biochemistry molecular biology. Keyword co-occurrence and co-citation clustering analysis revealed that studies of MSC-EVs covered cellular origin (bone marrow mesenchymal stem cell, adipose-derived mesenchymal stem cell), injurious diseases (spinal cord injury, acute lung injury, ischemia/reperfusion injury, acute kidney injury, traumatic brain injury), tumor (breast cancer, tumor microenvironment), biological processes (drug delivery system, angiogenesis, inflammation, proliferation, differentiation, senescence), and molecular mechanisms (signaling pathway, signal transduction, oxidative stress, VEGF, TGF β). Conclusions: Studies on MSC-EVs have shown a steep growth trend in recent years. Available studies mostly focused on the therapeutic effects and underlying mechanisms of MSC-EVs in aplastic diseases. Multidisciplinary integration is a development trend in this field, and senescence-related topics might be the focus of future research on MSC-EVs.